Fixed point theorems for densifying mappings and compact mappings - Zeqing Liu; Li Wang; Shin Min Kang; Yong Soo Kim (International Journal of Mathematics and Mathematical Sciences)
The purpose of this note is to establish fixed point theorems for densifying mappings and compact mappings which are contractive in metric spaces and to investigate the existence of fixed points for a family of mappings in bounded metric spaces. The results of this note generalize the results of Bailey (1966) and Liu (1994).